2022
DOI: 10.3390/f13030384
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Loading Distance, Loading Angle and Log Orientation on Time Consumption of Forwarder Loading Cycles: A Pilot Case Study

Abstract: Fully mechanized timber harvesting systems are well established in forest operations worldwide. In cut-to-length (CTL) systems, forwarders are used for extracting logs from the stand. The productivity of a forwarder is related to site- and stand-specific characteristics, technical parameters, organizational aspects, and the individual skills of the operator. The operator’s performance during “loading” considerably affects forwarder productivity, since this element occupies nearly 50% of forwarding cycle time i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 28 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…"Negative" positioning, i.e., too far a distance between the machine and the tree to be harvested (harvester), or the wood pile to be loaded (forwarder), leads to increased wear and tear of the crane elements and also to decreased productivity due to longer crane paths. This is in line with other studies which revealed that increasing loading distances can have a negative impact on time consumption per loading cycle [27], and therefore productivity. Since the loading element is the most important [23] to productivity, adequate positioning towards reducing time consumption during loading is worth striving for.…”
Section: Discussion: Interviewssupporting
confidence: 93%
See 4 more Smart Citations
“…"Negative" positioning, i.e., too far a distance between the machine and the tree to be harvested (harvester), or the wood pile to be loaded (forwarder), leads to increased wear and tear of the crane elements and also to decreased productivity due to longer crane paths. This is in line with other studies which revealed that increasing loading distances can have a negative impact on time consumption per loading cycle [27], and therefore productivity. Since the loading element is the most important [23] to productivity, adequate positioning towards reducing time consumption during loading is worth striving for.…”
Section: Discussion: Interviewssupporting
confidence: 93%
“…The literature search on forwarder operators showed that loading is the primary interest of the retrieved studies. [27] found log and loading angles of 45 • as most beneficial within a work range of 4-6 m for a certain machine type. Moreover, the grapple load was analyzed in another study, and the assortment pile size should match the maximum grapple load, to ensure efficient handling [4].…”
Section: Synthesis and Evaluationmentioning
confidence: 91%
See 3 more Smart Citations